Implementasi Sistem Irigasi Berbasis Internet of Things (IoT) Untuk Optimasi Penggunaan Air Pada Pertanian - Haj, Shafly Ulya; Adek, Rizal Tjut; Suwanda, Rizki (METIK JURNAL (AKREDITASI SINTA 3), 2025)
Traditional irrigation systems in Indonesia's agricultural sector still face obstacles in water use efficiency. This research aims to develop an Internet of things (IoT)-based automatic irrigation system capable of monitoring and controlling soil moisture and water level in real-time. The system is designed using an ESP32 microcontroller, two soil moisture sensors, and one ultrasonic sensor integrated with a servo motor actuator. Rule-based control logic is applied, where the sluice gates open when the moisture is < 50% and the water level is > 25 cm, and close again when the opposite condition occurs. The prototype was tested on two simulated paddy fields with glass aquarium media for three days and five recording cycles. Data was sent to the server and displayed via a web interface for remote monitoring and control. The test results show that the system is able to work responsively, with an average response time of 1.8 seconds, and can increase water use efficiency by 30%. The graph visualisation and manual-automatic control features provide ease of system management. The application of this system shows great potential in supporting the implementation of efficient, scalable, and sustainable precision agriculture.